A high-entropy wear-resistant coating with a wide temperature range and a preparation method thereof
By spraying (HfMoNbTaTi)C high-entropy ceramic phase on the CrFeNiAl0.3Ti0.3 high-entropy alloy matrix, CrFeNiAl0.3Ti0.3 high-entropy wear-resistant coating is formed, which solves the problem of insufficient performance of high-entropy wear-resistant coating in a wide temperature domain, and achieves excellent mechanical and wear-resistant performance under high temperature conditions.
Patent Information
- Application Number
- CN202411200105.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-08-29
AI Technical Summary
The prior art is difficult to provide high entropy wear-resistant coatings with excellent performance in a wide temperature range, especially under high temperature conditions.
CrFeNiAl0.3Ti0.3 high-entropy alloy was used as the matrix, and 5~20 wt.% of (HfMoNbTaTi)C high-entropy ceramic phase was sprayed on its surface, and CrFeNiAl0.3Ti0.3-Al-(HfMoNbTaTi)C high-entropy wear-resistant coating was formed by explosive spraying.
The coating exhibits excellent mechanical properties and wear resistance in a wide temperature range from room temperature to 800°C. It has a simple, controllable process and low cost, making it suitable for mass production.
Smart Images

Figure CN118932272B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of advanced coating materials and surface engineering technology, and in particular to a wide temperature range high entropy wear-resistant coating and a preparation method thereof. Background Art
[0002] High temperature is one of the most demanding working conditions for mechanical systems. High-performance new materials and advanced surface engineering technologies play an important leading and supporting role in promoting the sustainable and innovative development of advanced manufacturing industries represented by aerospace and nuclear energy. In recent years, the new high-entropy concept has brought new inspiration to the design and development of lubricating and wear-resistant coating materials: (1) Multi-component characteristics provide materials with a wider range of composition and organizational regulation space, promoting the formation of medium-low temperature gradient wear-resistant layers and high-temperature wear-resistant enamel layers (cocktail effect); (2) Thermodynamic high entropy, structural lattice distortion and kinetic hysteresis diffusion effects enable materials to have excellent thermal stability and combined toughness / plasticity properties over a wide temperature range.
[0003] In terms of wide temperature range mechanical properties, the design concept of Cr-Fe-Ni-Al-Ti high entropy alloy is to introduce Ti and Al elements into FCC structure CrFeNi alloy to induce the formation of BCC and L21 phases, so that the alloy can achieve an excellent combination of strength and ductility in the temperature range from room temperature to 900 ºC. Its high temperature mechanical properties are better than those of ferritic superalloys, and it can achieve mechanical properties comparable to Inconel 617 / 718 high temperature alloys at a lower cost (Acta Materialia, 2021, 211: 116890; Acta Materialia, 2021, 216: 117113).
[0004] In terms of wide temperature range wear resistance, composite second phase hard / ceramic phase is one of the most reliable means to improve the wear resistance of coatings. Common hard phases mainly include oxides, carbides, etc. Recently, a single-phase (HfMoNbTaTi)C high entropy ceramic was reported to have high hardness, mechanical properties and wide temperature range wear resistance (TrbolologyInternational, 2021, 157: 106883), which may be a new type of hard / ceramic second phase material. Therefore, the present invention expects to use the (HfMoNbTaTi)C high entropy ceramic as a toughening and wear-resistant phase to prepare a new wear-resistant coating. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a high-entropy wear-resistant coating with excellent performance in a wide temperature range.
[0006] Another technical problem to be solved by the present invention is to provide a method for preparing the wide temperature range high entropy wear-resistant coating.
[0007] In order to solve the above problems, the invention discloses a wide temperature range high entropy wear-resistant coating, characterized in that: the wear-resistant coating is CrFeNiAl 0.3 Ti 0.3 -Al-(HfMoNbTaTi)C high entropy wear-resistant coating, the composition of which is 10% Al, 5-20% (HfMoNbTaTi)C high entropy ceramic phase and the rest CrFeNiAl 0.3 Ti 0.3 High entropy alloy phase composition.
[0008] The method for preparing a wide temperature range high entropy wear-resistant coating as described above comprises the following steps:
[0009] ⑴ Weigh CrFeNiAl according to the mass ratio 0.3 Ti 0.3 High entropy alloy powder, Al powder and (HfMoNbTaTi)C high entropy ceramic powder are placed in a ball mill and loaded into a low-energy ball mill for uniform mixing, with a ball-to-material ratio of 1:2-1:1 and a time of 2-3 h to obtain a spray composite powder;
[0010] (2) The metal substrate is first polished with 200 mesh, 400 mesh, and 800 mesh sandpaper in sequence, then ultrasonically cleaned and dried, and then the surface of the metal substrate is roughened with a high-pressure sandblasting machine. After ultrasonic cleaning and drying, the treated metal substrate is obtained;
[0011] ⑶ The treated metal substrate is preheated at 200-400° C. to obtain a preheated metal substrate;
[0012] (4) loading NiCrAlY powder into a powder feeder, and spraying a NiCrAlY transition layer with a thickness of 90-120 μm on the surface of the preheated metal substrate by using an explosion spraying process;
[0013] (5) The spray composite powder is placed in a powder feeder, and a CrFeNiAl with a thickness of 100-450 μm is prepared on the surface of the NiCrAlY transition layer by an explosion spraying process. 0.3 Ti 0.3 -Al-(HfMoNbTaTi)C wear-resistant coating.
[0014] In the step (1), CrFeNiAl 0.3 Ti 0.3 The high entropy alloy powder is spherical with a particle size of 10~55 μm.
[0015] In the step (1), the Al powder is spherical and has a particle size of 10-65 μm.
[0016] In the step (⑴), the (HfMoNbTaTi)C high entropy ceramic powder is an irregular granular powder with a particle size of 10-35 μm, and is composed of 10-12.5 wt.% Hf, 10-12.5 wt.% Mo, 10-12.5 wt.% Nb, 10-12.5 wt.% Ta, 10-12.5 wt.% Ti and 37.5-50 wt.% C.
[0017] In step (2), the metal matrix refers to one of stainless steel, titanium alloy and nickel-based high-temperature alloy.
[0018] In the step (4), the NiCrAlY powder is spherical and has a particle size of 18-63 μm.
[0019] The conditions for explosion spraying in step (2) and step (4) are that the oxygen-carbon ratio of the explosion gas mixture is 1.251:1~1.315:1, the fuel gas components are acetylene and propane, the inflation volume is 55%~65%, pulse powder feeding and ignition are adopted, the spraying frequency is 2.5~5.5 Hz, the powder feeding rate is 2.5 g / shot, the spraying distance is 150~250mm, and nitrogen is used as the powder feeding carrier gas and protective gas.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1. The present invention adopts CrFeNiAl with excellent strength and plasticity at room temperature to 800 ℃ 0.3 Ti 0.3 The high entropy alloy is used as the matrix, which makes the coating have excellent mechanical properties in a wide temperature range; the new single-phase (HfMoNbTaTi)C high entropy ceramic is selected as the toughening and wear-resistant phase, which can effectively improve the wear resistance in a wide temperature range; the Al element is selected as CrFeNiAl 0.3 Ti 0.3 The binder between the high entropy alloy and the (HfMoNbTaTi)C high entropy ceramic improves the density of the coating and, on the other hand, is beneficial to the formation of an Al2O3-rich enamel layer during high-temperature sliding.
[0022] 2. Since carbides are easily decomposed at high temperatures, the present invention adopts the explosion spraying process to effectively inhibit the decomposition of carbides, ensuring that the (HfMoNbTaTi)C high entropy ceramics are 0.3 Ti 0.3 Phase structure and chemical stability in high entropy alloys.
[0023] 3. The preparation process of the present invention is simple, controllable, low-cost, and can be mass-produced. The prepared coating has excellent wear resistance in a wide temperature range of 25 to 800 °C, and has important application prospects in high-temperature wear-resistant applications of motion transmission parts in high-tech fields such as aerospace. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.
[0025] Figure 1 CrFeNiAl prepared in Examples 1 to 3 of the present invention 0.3 Ti 0.3 -XRD diffraction pattern of Al-(HfMoNbTaTi)C wear-resistant coating.
[0026] Figure 2 The CrFeNiAl prepared in Example 3 of the present invention 0.3 Ti 0.3 -10 wt. %Al-20 wt. %(HfMoNbTaTi)C high entropy wear-resistant coating surface microstructure photograph and element distribution map.
[0027] Figure 3 The CrFeNiAl prepared in Example 3 of the present invention 0.3 Ti 0.3 -10 wt. %Al-20 wt. %(HfMoNbTaTi)C high entropy wear-resistant coating cross-section microstructure photograph and element distribution map.
[0028] Figure 4 CrFeNiAl prepared in Examples 1 to 3 of the present invention 0.3 Ti 0.3 -Wear rate of Al-(HfMoNbTaTi)C high entropy wear resistant coating.
[0029] Figure 5 CrFeNiAl prepared in Examples 1 to 3 of the present invention 0.3 Ti 0.3 -Friction coefficient of Al-(HfMoNbTaTi)C high entropy wear resistant coating. DETAILED DESCRIPTION
[0030] A high entropy wear-resistant coating with a wide temperature range, the wear-resistant coating is CrFeNiAl 0.3 Ti 0.3 -Al-(HfMoNbTaTi)C high entropy wear-resistant coating, the composition of which is 10% Al by mass fraction (g), 5-20% (HfMoNbTaTi)C high entropy ceramic phase and the rest CrFeNiAl 0.3 Ti 0.3 High entropy alloy phase composition.
[0031] The preparation method thereof comprises the following steps:
[0032] ⑴ Weigh CrFeNiAl according to the mass ratio0.3 Ti 0.3 High entropy alloy powder, Al powder and (HfMoNbTaTi)C high entropy ceramic powder were placed in a ball mill and loaded into a low-energy ball mill for uniform mixing, with a ball-to-material ratio (g / g) of 1:2~1:1 and a mixing time of 2~3 h to obtain a spray composite powder.
[0033] Among them: CrFeNiAl 0.3 Ti 0.3 The high entropy alloy powder is spherical with a particle size of 10~55 μm.
[0034] The Al powder is spherical and has a particle size of 10~65 μm.
[0035] The (HfMoNbTaTi)C high entropy ceramic powder is an irregular granular powder with a particle size of 10~35 μm, and is composed of 10~12.5wt.% Hf, 10~12.5 wt.% Mo, 10~12.5 wt.% Nb, 10~12.5 wt.% Ta, 10~12.5 wt.% Ti and 37.5~50 wt.% C.
[0036] (2) The metal substrate is first polished with 200 mesh, 400 mesh, and 800 mesh sandpaper, then ultrasonically cleaned and dried, and then the surface of the metal substrate is roughened with a high-pressure sandblasting machine. After ultrasonic cleaning and drying, the treated metal substrate is obtained. The metal substrate refers to one of stainless steel, titanium alloy, and nickel-based high-temperature alloy.
[0037] ⑶ The treated metal substrate is preheated at 200~400°C to obtain a preheated metal substrate.
[0038] (4) Load NiCrAlY powder into the powder feeder, and when the oxygen-carbon ratio (mL / mL) of the explosion gas mixture is 1.251:1~1.315:1, the fuel gas composition is acetylene and propane, the filling volume is 55%~65%, pulse powder feeding and ignition are adopted, the spraying frequency is 2.5~5.5 Hz, the powder feeding rate is 2.5 g / shot, the spraying distance is 150~250mm, and nitrogen is used as the powder feeding carrier gas and protective gas. A NiCrAlY transition layer with a thickness of 90~120 μm is sprayed on the preheated metal substrate surface by explosion spraying process.
[0039] The NiCrAlY powder is spherical with a particle size of 18~63 μm.
[0040] ⑸ The spray composite powder was placed in a powder feeder, and the explosion gas mixed oxygen-carbon ratio (mL / mL) was 1.251:1~1.315:1, the fuel gas composition was acetylene and propane, the filling volume was 55%~65%, pulse powder feeding and ignition were adopted, the spraying frequency was 2.5~5.5 Hz, the powder feeding rate was 2.5 g / shot, the spraying distance was 150~250mm, and nitrogen was used as the powder feeding carrier gas and protective gas. The CrFeNiAl with a thickness of 100~450μm was prepared on the surface of the NiCrAlY transition layer by explosion spraying process. 0.3 Ti 0.3 -Al-(HfMoNbTaTi)C wear-resistant coating.
[0041] Example 1 Preparation of CrFeNiAl 0.3 Ti 0.3 -10 wt. % Al high entropy alloy based wear-resistant coating:
[0042] ⑴ Weigh 90 g CrFeNiAl 0.3 Ti 0.3 High entropy alloy powder and 10 g Al powder were placed in a ball mill and loaded into a low-energy ball mill for uniform mixing with a ball-to-material ratio (g / g) of 1:1 for 2 h to obtain a spray composite powder.
[0043] Among them: CrFeNiAl 0.3 Ti 0.3 The high entropy alloy powder is spherical and has a particle size of 35 μm.
[0044] The Al powder is spherical and has a particle size of 10 μm.
[0045] (2) The 304L metal substrate is first polished with 200 mesh, 400 mesh and 800 mesh sandpaper in sequence, then ultrasonically cleaned and dried, and then the surface of the metal substrate is roughened with a high-pressure sandblasting machine. After ultrasonic cleaning and drying, the treated metal substrate is obtained.
[0046] ⑶ The treated metal substrate is preheated at 200°C to obtain a preheated metal substrate.
[0047] (4) Load 100 g of NiCrAlY powder with a particle size of 18 μm into the powder feeder. Under the conditions of explosive gas (gas components are acetylene and propane) and oxygen mixed with an oxygen-carbon ratio (mL / mL) of 1:1.255, a gas filling volume of 57%, a spraying frequency of 3 Hz, a powder feeding rate of 2 g / shot, a spraying distance of 250 mm, and nitrogen as the powder carrier gas and protective gas, a NiCrAlY transition layer with a thickness of 90 μm was sprayed on the preheated metal substrate surface by explosion spraying process.
[0048] ⑸ The spray composite powder was placed in a powder feeder, and a CrFeNiAl with a thickness of 100 μm was prepared on the surface of the NiCrAlY transition layer by explosion spraying process under the conditions of explosive gas (gas components are acetylene and propane) and oxygen mixed with oxygen carbon ratio (mL / mL) of 1:1.255, gas filling volume of 57%, spraying frequency of 3 Hz, powder feeding rate of 2 g / shot, spraying distance of 250 mm, and nitrogen as powder feeding carrier gas and protective gas. 0.3 Ti 0.3 -10 wt. % Al high entropy alloy based wear-resistant coating.
[0049] CrFeNiAl 0.3 Ti 0.3 -10 wt. % Al high entropy alloy based wear resistant coating was analyzed by X-ray diffractometer (XRD) to analyze its phase structure and chemical composition, such as Figure 1 As shown. Figure 1 It can be seen that its main phases include BCC, FCC phase and pure Al phase.
[0050] CrFeNiAl 0.3 Ti 0.3 The tribological properties of the -10 wt. % Al high entropy alloy-based wear-resistant coating were tested using a GF-I high-temperature friction tester. The mating material was a Si3N4 ceramic ball with a diameter of 6 mm. The test temperatures were 25 ℃, 400 ℃, and 800 ℃, the sliding speed was 0.1 m / s, the load was 1 0N, and the test time was 30 min. The results are shown in Table 1. Figures 4 and 5 shown.
[0051] Table 1 Friction performance
[0052]
[0053] From Table 1, Figures 4 and 5 It can be seen that the friction coefficient of the obtained coating is stable at 0.52 ~ 0.70 from room temperature to 800 °C; the wear is maintained at 3.052 ~ 33.98 × 10 -5 (mm 3 / Nm).
[0054] Example 2 Preparation of CrFeNiAl 0.3 Ti 0.3 -10 wt. % Al-10 wt.% (HfMoNbTaTi)C high entropy wear resistant coating:
[0055] ⑴ Weigh 80 g CrFeNiAl 0.3 Ti 0.3High entropy alloy powder, 10 g Al powder and 10 g (HfMoNbTaTi)C high entropy ceramic powder were placed in a ball mill and loaded into a low-energy ball mill for uniform mixing with a ball-to-material ratio (g / g) of 1:1 for 3 h to obtain a spray composite powder.
[0056] Among them: CrFeNiAl 0.3 Ti 0.3 The high entropy alloy powder is spherical and has a particle size of 10 μm.
[0057] The Al powder is spherical and has a particle size of 45 μm.
[0058] The (HfMoNbTaTi)C high entropy ceramic powder is an irregular granular powder with a particle size of 27 μm, and is composed of 12.5 g Hf, 12.5 g Mo, 12.5 g Nb, 12.5 g Ta, 12.5 g Ti and 37.5 g C.
[0059] (2) The 304L metal substrate is first polished with 200 mesh, 400 mesh and 800 mesh sandpaper in sequence, then ultrasonically cleaned and dried, and then the surface of the metal substrate is roughened with a high-pressure sandblasting machine. After ultrasonic cleaning and drying, the treated metal substrate is obtained.
[0060] ⑶ The treated metal substrate is preheated at 300°C to obtain a preheated metal substrate.
[0061] (4) Load 100 g NiCrAlY powder with a particle size of 55 μm into the powder feeder. Under the conditions of explosive gas (gas components are acetylene and propane) and oxygen mixed with an oxygen-carbon ratio (mL / mL) of 1:1.285, aeration volume of 60%, spraying frequency of 4 Hz, powder feeding rate of 2 g / shot, spraying distance of 200 mm, and nitrogen as powder carrier gas and protective gas, a NiCrAlY transition layer with a thickness of 110 μm was sprayed on the preheated metal substrate surface by explosion spraying process.
[0062] ⑸ The spray composite powder was placed in a powder feeder, and a CrFeNiAl with a thickness of 350 μm was prepared on the surface of the NiCrAlY transition layer by explosion spraying process under the conditions of explosive gas (gas components are acetylene and propane) and oxygen mixed with oxygen and oxygen with an oxygen-carbon ratio (mL / mL) of 1:1.285, a gas filling volume of 60%, a spraying frequency of 4 Hz, a powder feeding rate of 2 g / shot, a spraying distance of 200 mm, and nitrogen as a powder feeding carrier gas and a protective gas. 0.3 Ti 0.3 -10 wt. % Al-10 wt.% (HfMoNbTaTi)C high entropy wear resistant coating.
[0063] CrFeNiAl 0.3 Ti 0.3 -10 wt. % Al-10 wt.% (HfMoNbTaTi)C high entropy wear resistant coating was analyzed by X-ray diffractometer (XRD) to analyze its phase structure and chemical composition, such as Figure 1 As shown. Figure 1 It can be seen that its main phases include BCC, FCC phase, pure Al phase and (HfMoNbTaTi)C high entropy ceramic phase.
[0064] CrFeNiAl 0.3 Ti 0.3 -10 wt.% Al-10 wt.% (HfMoNbTaTi)C high entropy wear-resistant coating was subjected to tribological performance test. The test method was the same as that in Example 1. The results are shown in Table 2. Figures 4 and 5 shown.
[0065] Table 2 Friction performance
[0066]
[0067] From Table 2, Figures 4 and 5 It can be seen that the friction coefficient of the obtained coating is stable at 0.54 ~ 0.68 from room temperature to 800 °C; the wear is maintained at 0.99 ~ 11.00 × 10 -5 (mm 3 / Nm).
[0068] Example 3 Preparation of CrFeNiAl 0.3 Ti 0.3 -10 wt. %Al-20 wt. % (HfMoNbTaTi)C high entropy wear resistant coating:
[0069] ⑴ Weigh 70 g CrFeNiAl 0.3 Ti 0.3 High entropy alloy powder, 10 g Al powder and 20 g (HfMoNbTaTi)C high entropy ceramic powder were placed in a ball mill and loaded into a low-energy ball mill for uniform mixing with a ball-to-material ratio (g / g) of 1:2 for 3 h to obtain a spray composite powder.
[0070] Among them: CrFeNiAl 0.3 Ti 0.3 The high entropy alloy powder is spherical and has a particle size of 55 μm.
[0071] The Al powder is spherical and has a particle size of 65 μm.
[0072] The (HfMoNbTaTi)C high entropy ceramic powder is an irregular granular powder with a particle size of 35 μm, and is composed of 11.5 g Hf, 11.5 g Mo, 11.5 g Nb, 11.5 g Ta, 11.5 g Ti and 42.5 g C.
[0073] (2) The 304L metal substrate is first polished with 200 mesh, 400 mesh and 800 mesh sandpaper in sequence, then ultrasonically cleaned and dried, and then the surface of the metal substrate is roughened with a high-pressure sandblasting machine. After ultrasonic cleaning and drying, the treated metal substrate is obtained.
[0074] ⑶ The treated metal substrate is preheated at 300°C to obtain a preheated metal substrate.
[0075] (4) Load 100 g NiCrAlY powder with a particle size of 63 μm into the powder feeder. Under the conditions of explosive gas (gas components are acetylene and propane) and oxygen mixed with an oxygen-carbon ratio (mL / mL) of 1:1.315, a gas filling volume of 65%, a spraying frequency of 5 Hz, a powder feeding rate of 2 g / shot, a spraying distance of 150 mm, and nitrogen as the powder carrier gas and protective gas, a NiCrAlY transition layer with a thickness of 120 μm is sprayed on the preheated metal substrate surface by explosion spraying process.
[0076] ⑸ The spray composite powder was placed in a powder feeder, and a CrFeNiAl with a thickness of 450 μm was prepared on the surface of the NiCrAlY transition layer by explosion spraying process under the conditions of explosive gas (gas components are acetylene and propane) and oxygen mixed with oxygen carbon ratio (mL / mL) of 1:1.315, gas filling volume of 65%, spraying frequency of 5 Hz, powder feeding rate of 2 g / shot, spraying distance of 150 mm, and nitrogen as powder feeding carrier gas and protective gas. 0.3 Ti 0.3 -10 wt. %Al-20 wt. % (HfMoNbTaTi)C high entropy wear resistant coating.
[0077] CrFeNiAl 0.3 Ti 0.3 -10 wt. %Al-20 wt. % (HfMoNbTaTi)C high entropy wear-resistant coating was analyzed by X-ray diffractometer (XRD) to analyze its phase structure and chemical composition, such as Figure 1 As shown. Figure 1 It can be seen that its main phases include BCC, FCC phase, pure Al phase and (HfMoNbTaTi)C high entropy ceramic phase.
[0078] CrFeNiAl 0.3 Ti0.3 -10 wt. %Al-20 wt. % (HfMoNbTaTi)C high entropy wear-resistant coating was characterized by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS), such as Figure 2~3 As shown in the figure, it can be seen that the (HfMoNbTaTi)C high entropy ceramic phase is evenly distributed in the CrFeNiAl 0.3 Ti 0.3 -10 wt. %Al-20 wt. % (HfMoNbTaTi)C high entropy wear resistant coating.
[0079] CrFeNiAl 0.3 Ti 0.3 -10 wt. %Al-20 wt. % (HfMoNbTaTi)C high entropy wear-resistant coating was tested for tribological properties. The test method was the same as in Example 1. The results are shown in Table 3. Figures 4 and 5 shown.
[0080] Table 3 Friction performance
[0081]
[0082] From Table 3, Figures 4 and 5 It can be seen that the friction coefficient of the obtained coating is stable at 0.53 ~ 0.7 from room temperature to 800 °C; the wear is maintained at 2.30 ~ 8.96 × 10 -5 (mm 3 / Nm).
Claims
1. A high-entropy wear-resistant coating with a wide temperature range, characterized in that: The wear-resistant coating is CrFeNiAl 0.3 Ti 0.3 -Al-(HfMoNbTaTi)C high entropy wear-resistant coating, the composition of which is 10% Al, 5-20% (HfMoNbTaTi)C high entropy ceramic phase and the rest CrFeNiAl 0.3 Ti 0.3 High entropy alloy phase composition; Al as CrFeNiAl 0.3 Ti 0.3 The binder between the high entropy alloy and the (HfMoNbTaTi)C high entropy ceramic improves the density of the coating and forms an Al2O3-rich enamel layer during high-temperature sliding. The wear-resistant coating is weighed according to the mass ratio of CrFeNiAl 0.3 Ti 0.3 High entropy alloy powder, Al powder and (HfMoNbTaTi)C high entropy ceramic powder are placed in a ball mill and loaded into a low-energy ball mill for uniform mixing to obtain a spray composite powder, which is then prepared on the surface of a NiCrAlY transition layer using a detonation spraying process.
2. The method for preparing a wide temperature range high entropy wear-resistant coating according to claim 1, comprising the following steps: ⑴ Weigh CrFeNiAl according to the mass ratio 0.3 Ti 0.3 High entropy alloy powder, Al powder and (HfMoNbTaTi)C high entropy ceramic powder are placed in a ball mill and loaded into a low-energy ball mill for uniform mixing, with a ball-to-material ratio of 1:2-1:1 and a time of 2-3 h to obtain a spray composite powder; (2) The metal substrate is first polished with 200 mesh, 400 mesh, and 800 mesh sandpaper in sequence, then ultrasonically cleaned and dried, and then the surface of the metal substrate is roughened with a high-pressure sandblasting machine. After ultrasonic cleaning and drying, the treated metal substrate is obtained; ⑶ The treated metal substrate is preheated at 200-400° C. to obtain a preheated metal substrate; (4) loading NiCrAlY powder into a powder feeder, and spraying a NiCrAlY transition layer with a thickness of 90-120 μm on the surface of the preheated metal substrate by using an explosion spraying process; (5) The spray composite powder is placed in a powder feeder, and a CrFeNiAl with a thickness of 100-450 μm is prepared on the surface of the NiCrAlY transition layer by an explosion spraying process. 0.3 Ti 0.3 -Al-(HfMoNbTaTi)C wear-resistant coating.
3. The method for preparing a wide temperature range high entropy wear-resistant coating according to claim 2, characterized in that: In the step (1), CrFeNiAl 0.3 Ti 0.3 The high entropy alloy powder is spherical with a particle size of 10~55 μm.
4. The method for preparing a wide temperature range high entropy wear-resistant coating according to claim 2, characterized in that: In the step (1), the Al powder is spherical and has a particle size of 10-65 μm.
5. The method for preparing a wide temperature range high entropy wear-resistant coating according to claim 2, characterized in that: In the step (⑴), the (HfMoNbTaTi)C high entropy ceramic powder is an irregular granular powder with a particle size of 10-35 μm, and is composed of 10-12.5 wt.% Hf, 10-12.5 wt.% Mo, 10-12.5 wt.% Nb, 10-12.5 wt.% Ta, 10-12.5 wt.% Ti and 37.5-50wt.% C.
6. The method for preparing a wide temperature range high entropy wear-resistant coating according to claim 2, characterized in that: In step (2), the metal matrix refers to one of stainless steel, titanium alloy and nickel-based high-temperature alloy.
7. The method for preparing a wide temperature range high entropy wear-resistant coating according to claim 2, characterized in that: In the step (4), the NiCrAlY powder is spherical and has a particle size of 18-63 μm.
8. The method for preparing a wide temperature range high entropy wear-resistant coating according to claim 2, characterized in that: The conditions for explosion spraying in step (2) and step (4) are that the oxygen-carbon ratio of the explosion gas mixture is 1.251:1~1.315:1, the fuel gas components are acetylene and propane, the inflation volume is 55%~65%, pulse powder feeding and ignition are adopted, the spraying frequency is 2.5~5.5Hz, the powder feeding rate is 2.5 g / shot, the spraying distance is 150~250 mm, and nitrogen is used as the powder feeding carrier gas and protective gas.
Citation Information
Patent Citations
Easy-to-sinter wear-resistant friction-reducing high-entropy ceramic material and preparation method thereof
CN114031406A
Preparation method of wide-temperature-range high-entropy alloy-based self-lubricating coating
CN118064822A